Exposure to DEHP or its metabolite MEHP promotes progesterone secretion and inhibits proliferation in mouse placenta or JEG-3 cells. (February 2020) - Zhang, Shanyu; Sun, Congcong; Zhao, Shuai; Wang, Bo; Wang, Hua; Zhang, Jun; Wang, Yang; Cheng, Hanchao; Zhu, Liya; Shen, Ru; Sun, Meifang; Xu, Tao; et al.
Abstract: Di (2-ethyl-hexyl)phthalate (DEHP) is an environmental endocrine disruptor and commonly used as plasticizer. Maternal DEHP exposure during pregnancy reduces placental size and destroys placental structure. However, the underlying mechanisms were unclear. In this study, we supposed that DEHP disturbs endocrine function of placenta to inhibit the proliferation of placental cell. Using radioimmunoassay and ELISA, we found that DEHP and its active metabolite mono (2-ethyl-hexyl) phthalate (MEHP) promoted progesterone secretion in pregnant mouse and in JEG-3 cells, respectively. Therefore, placental endocrine function was altered by DEHP. The mRNA and protein level of progesterone synthetase 3β-HSD1 was elevated by DEHP, which is conducive to the synthesis of progesterone. The level of progesterone receptor was down-regulated by DEHP and MEHP in mouse placenta and in JEG-3 cells, respectively. PR deficiency further promoted the level of 3β-HSD1, which leads to a higher progesterone level. In turn, higher concentration of progesterone further inhibited the expression of PGR (PR gene). Therefore, higher progesterone down-regulated the level of its receptor PR. Meanwhile, decreased PR induced more progesterone secretion. There is a feedback loop between progesterone and PR. PR deficiency down-regulated the protein level of Cyclin D1 which plays an important role in cell proliferation. Accordingly, DEHP and its active metabolite MEHP can restrain proliferation of placental cell and disturb the progesterone secretion via decreasing the level of PR. Graphical abstract: Image 109176 Highlights: Maternal DEHP exposure during pregnancy raised progesterone secretion from placenta in mouse. There is a feedback loop between progesterone and PR in JEG-3 cells treated with MEHP, the active metabolite of DEHP. High concentrations of progesterone are not always beneficial to placental function. Abstract : Exposure to DEHP or its metabolite MEHP improves progesterone level and inhibits proliferation in mouse placenta or JEG-3 cells.